Perempuan sebagai Proksi Kekuasaan: Representasi Gender dalam Politik Dinasti Lokal - Febrianto Syam; Ismah Tita Ruslin; Novayanti Sopia Rukmana S; Ummi Suci Fathia Bailusy (Society, 2025)
The presence of women in the political sphere is often celebrated as an achievement in the agenda of gender equality and democratization. However, such representation does not always reflect true political independence. In many cases at the local level, women’s involvement forms part of a dynastic political strategy that relies on kinship ties to maintain power. This research examines how women are used as proxies of power within the context of dynastic politics rooted in patriarchal structures. Using a qualitative approach and a case study design, this research explores the symbolic representation practices of a female political actor in a region in South Sulawesi. She advanced in the political contest with strong support from a family power network that has long dominated the local political landscape. Through a theoretical framework on dynastic politics and power proxies, this study reveals that women’s involvement does not always strengthen empowerment agendas but can instead serve as an instrument for perpetuating family power dominance. These findings highlight the ambiguity between representation and empowerment, as well as the importance of distinguishing women’s symbolic presence from participation based on individual autonomy and capacity. This study contributes to a critical understanding of the relationship between gender, power, and the persistence of dynastic politics in local electoral democracy.